Contribution of GABAergic interneurons to amyloid-β plaque pathology in an APP knock-in mouse model - Rice, Heather; Marcassa, Gabriele; Chrysidou, Iordana; Horré, Katrien; Young-Pearse, Tracy L.; Müller, Ulrike C.; Saito, Takashi; Saido, Takaomi C.; Vassar, Robert; de Wit, Joris; De Strooper, Bart (Molecular neurodegeneration, 2020)
The amyloid-β (Aβ) peptide, the primary constituent of amyloid plaques found in Alzheimer’s disease (AD) brains, is derived from sequential proteolytic processing of the Amyloid Precursor Protein (APP). However, the contribution of different cell types to Aβ deposition has not yet been examined in an in vivo, non-overexpression system. Here, we show that endogenous APP is highly expressed in a heterogeneous subset of GABAergic interneurons throughout various laminae of the hippocampus, suggesting that these cells may have a profound contribution to AD plaque pathology.
Gesehen am 01.04.2020